Focus on Antibiotics – New Challenges and Steps Forward in Discovery and Development, 2nd Edition (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue, "Focus on Antibiotics – New Challenges and Steps Forward in Discovery and Development, 2nd Edition," explores innovative strategies and groundbreaking research to combat antibiotic resistance. Key advancements include enhancing antibacterial drug potency, selectivity, and safety through five-membered heterocycles; using phytocannabinoids like cannabigerol for MRSA biofilm inhibition; employing ZnONPs and AuNPs to combat MDR pathogens; developing Bac10307-AgNPs with potent antibacterial and antioxidant properties; creating fluoroquinolone co-crystals with flavonoids for enhanced antimicrobial activity; synthesizing 6″-deoxykanamycin A analogues to improve activity against resistant Staphylococcus aureus; designing silver nanocomposites with significant antibacterial and antibiofilm activity; utilizing the insect AMP Tricoplusia ni cecropin A for colistin-resistant Escherichia coli with low cytotoxicity; and enhancing antimicrobial and antiviral activity with peptide [des-Cys11,Lys12,Lys13-(p-BthTX-I)2K] derivatives. This Special Issue showcases collaborative efforts to address antibiotic resistance, inspiring further research and development.